From Legal Protection towards Animal Rights: Between Moral and Legal Consciousness. Evolution of Approach on the Example of Administrative Case Law - Kalisz, Anna; Pawlicka, Dorota (Teisė, 2023)
This article undertakes to analyse the possibility and necessity of empowering animals, as ‘non-personal’ subjects of law, with subjectivity in Polish Law, and to indicate the relevant case-law of the courts (inter alia, administrative courts) in this regard. This article was prepared as part of the framework of the National Science Centre funded research project No. 2017/27/L/HS5/03245 Constitutional Consciousness as a Remedy for the Crisis of Discourse and Democracy Deficit in the European Union (No. DEC-2017/27/L/HS5/03245).
Keywords: social consciousness; sentient animals; legal protection of animals; animal rights; constitutional protection; administrative case law